Antibiogram Of Bacillus Cereus Isolated From Street Vended Foods In Srinagar Area Of Kashmir Valley - Hafiz, Yasir; Iqbal, Asif; Ahmad, Manzoor; Ali , Abid (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Bacteriological analysis was carried out on one hundred samples comprising of 60 mutton tikka and 40 chutney samples of five zones of Srinagar city of Jammu and Kashmir State. Food samples were collected from different vendors. Mannitol egg-yolk polymyxin-B sulfate agar (MEYPA) was used for isolation of Bacillus cereus. Out of 40 (40.00%) positive food samples 27 were of the mutton tikka and 13 of the chutney samples resulting in prevalence of 45% and 32.5%, respectively. The mean bacterial count of 60 mutton tikka and 40 chutney samples was 4.6817 and 5.6575 log10 cfu/g. The strains of Bacillus cereus were higly resistant to penicillin G (92.50%), an intermediatte resistance was noted against tetracycline (40.00%), linezolid (35.00%), erythromycin (32.5%), ampicillin (30.00%), and amoxycillin (25.00%). The most effective antibiotics against B. cereus included gentamicin (100%), ciprofloxacin (100%), chloramphenicol (90%) followed by streptomycin (80%).